Behaviors and experiences of nurses connected with professional work - Haor, Beata; Głowacka, Mariola; Ślusarz, Robert; Piotrowska, Anna (Nursing Problems / Problemy Pielęgniarstwa, 2014)
Introduction. Professional environment tends to be, for a nurse, a source of inspiration and professional satisfaction. Factors which may disturb the mental balance of a nurse and lead to professional burnout are connected, among others, with: conditions and organization of work, patient, co-operation with therapeutic staff, relations with a patient’s family, with work-related discomfort. Aim. The aim of the thesis was to analyze the determinants of chosen behavior patterns and experiences related with the work as a nurse. Material and methods. Analyses of chosen determinants of work-related behaviors and experiences conducted on the base of research among pediatric nurses. The methods used were: estimation, diagnostic survey, rating scale and questionnaire. Research tools were a standardized questionnaire of AVEM survey and a questionnaire survey of the author. Results and conclusions. The group of nurses surveyed was dominated by persons at risk of professional burnout syndrome. These are: type A with excessive workload and burned out type B. Typical work-related behaviors and experiencesin the group of pediatric nursesindicate a high risk of stress and professional burnout syndrome. Less active ways of problem-solving are observed in nurses with shorter service. Professional competences develop along with years of work. Nurses over 46 years of age are more likely to accept failures and to withdraw. Readiness to sacrifice own strength to fulfil professional tasks decreases along with the age of respondents. Nursing Topics 2014; 22 (2): 142–146